Modifikasi Topologi Pengendali PID untuk Automatic Voltage Regulator Generator Sinkron - Tri Dedi Pamungkas; Muhamad Haddin; Estiko Rijanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Automatic voltage regulator (AVR) is one of key elements in an excitation system which controls the synchronous generator terminal voltage in an electrical power generation plant. PID control algorithm in an AVR has been designed to obtain good response towards voltage reference without considering the effect of torque disturbance. This paper proposes a PID with modified topology for a digital AVR in order to regulate the generator terminal voltage in more speedy and more accurate, while maintaining robustness against torque disturbance. Performance of the digital AVR has been compared with conventional PID controller through experiments using a hardware in the loop (HIL) system. The experiment results show that the proposed PID with modified topology provides better performance than the conventional PID controller. Under torque disturbance, the proposed algorithm provides 83% smaller steady state error and 4.8 second shorter settling time compared to the conventional PID controller. When the reference voltage changes, compared to the conventional PID controller, the proposed algorithm provides 15% smaller steady state error, 79% smaller overshoot, and 0.2 second shorter settling time.